POTENSI DARI EKOWISATA SAGU (Metroxylon Sp.) DI NEGERI RUTONG, KECAMATAN LEITIMUR SELATAN, KOTA AMBON - Ririassa, Yoani; Lelloltery, Henderina; Seipalla, Billy (MARSEGU : Jurnal Sains dan Teknologi, 2024)
Sago Ecotourism is a type of tourism with the main attraction being Sago or Sago Forest which applies the sago conservation aspect in it which is supported by the creation of a State Regulation related to the preservation of the Sago Forest to avoid the use of sago which can lead to the destruction of the Sago Forest ecosystem for sago processing which is part of the Sago Ecotourism attraction. The Land of Rutong is one of the countries in Maluku that develops part of its sago forest to be used as a location for Sago Ecotourism as a potential that can be useful for tourists who visit. Therefore, this study aims to find out the potential of Sago Ecotourism in the Land of Rutong. This study uses a qualitative descriptive analysis method with data obtained through field observation at the location of Sago Ecotourism and interviews with sago ecotourism managers. The results of the study show that the potential of sago ecotourism in the country of rutong includes the ecosystem of the sago forest which has three types of sago trees, the sago processing process using traditional tools, and culinary tourism made from sago. This potential becomes an experience and a new source of knowledge that is different from other tourist attractions